Logan Honea: capstone - Honea, Logan, artist (Colorado State University. Libraries, 2024)
The artist's statement: As a graphic designer, I see design as a way to communicate, create meaningful connections, and invoke emotional responses. To me, design sparks conversations by creating powerful images with engaging concepts. It is important to capture people's attention and invite them to dive deeper into the meaning behind the work. Each project I curate is done with creativity, intent, and clarity from start to finish. I start my process by creating preliminary sketches by hand or on ProCreate, I then take it to a digital media like Adobe Illustrator to refine my ideas. After that I add specific details and work on type, color, and perfecting visual components. Starting my designs by hand allows me to experiment and explore creativity while giving a personal touch to the project. I believe that attention to detail is a key factor in design, so I strive to make the small things count whether I’m working on branding, publication, or digital designs. For example, in my Target Christmas campaign I focused on inclusivity and diversity of holiday traditions, making sure to include very specific elements for different holiday celebrations whether that meant making gingerbread houses, hanging stockings, lighting menorahs, or enjoying holiday dinners. Each window in this project was thought out and carefully crafted. My work is focused on crafting the right color palette and typography, and bringing attention to small elements to bring my designs and the client’s ideas to life. These little details and the thought behind them are what make my designs memorable. I strive to create designs that not only capture attention but also leave a lasting impression and make the audience think about why they were designed.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design